THE EFFECT OF THE USE OF INFORMATION TECHNOLOGY, EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS, AND TASK COMPLEXITY ON EMPLOYEE PERFORMANCE(Empirical Study on 4-Star Hotels in Badung Regency) - Putu Angel Shinta Lestari; Gede Juliarsa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The continuity of a company is highly determined by its employees’ performance. Performance improvement is affected by individual ability to utilize information technology effectively. This study aims to obtain empirical evidence regarding the effect of the use of information technology, the effectiveness of accounting information systems, and task complexity on employee performance. The research was conducted at 4-star hotels in Badung Regency, totaling 12 hotels, each employing 8–9 accounting staff. The population of this study consisted of 98 accounting employees from those 4-star hotels. The sampling technique used was saturated sampling, resulting in 65 respondents who met the criteria employees who had worked for more than one year and used the SAP (Systems, Applications, and Products in Data Processing) system. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that the use of information technology and the effectiveness of accounting information systems have a positive effect on employee performance, while task complexity has a negative effect on employee performance at 4-star hotels in Badung Regency. These findings emphasize the importance of improving information technology capability and accounting information system effectiveness in supporting employee performance within the hospitality industry.